Exploring mathematics self-efficacy levels among ninth-grade girls: A quantitative study - Wardat, Yousef; Elsayed, Abdelkader Mohamed; Alali, Rommel; Ismail, Abdelrahim Fathy (Journal of Education and e-Learning Research, 2026)
This study examined the level of mathematics self-efficacy among ninth-grade girls, with particular emphasis on geometry self-efficacy, and explored instructional practices that may enhance their confidence. A quantitative survey design was employed using a validated self-efficacy scale grounded in Bandura’s theory, focusing on the geometry unit in the ninth-grade mathematics curriculum. The instrument measured key dimensions of self-efficacy, including magnitude (task difficulty) and generality (transfer of confidence across tasks). The sample consisted of 105 ninth-grade girls selected from four randomly chosen classes in a private school during the first semester of the 2022/2023 academic year. Findings indicated a moderate overall level of mathematics self-efficacy. While participants demonstrated confidence in solving routine mathematical problems, their self-efficacy declined when addressing complex or unfamiliar geometry tasks. The results highlight the need to strengthen sources of self-efficacy, mastery experiences, vicarious experiences, verbal persuasion, and emotional regulation to support female students’ engagement in mathematics. Practical implications include implementing differentiated instruction, reinforcement strategies, hands-on geometry activities, and modeling practices. Additionally, curriculum developers and policymakers should integrate structured self-efficacy enhancing strategies within mathematics programs to foster sustained motivation and achievement among female learners.